A new species of Chaunus from Central Brazil : Anura; Bufonidae - Brandão, Reuber Albuquerque (2007)
A new species of Chaunus, apparently related to Chaunus arenarum, Chaunus rubescens, and Chaunus achavali is described. The new species occupies Cerrado habitats in southwestern Piauı´ and Bahia states and in northwestern Minas Gerais state, Brazil. The species is characterized by anterior interruption of the supraocular crest; weakly developed cranial crests; short and robust limbs; several pointed spiculae on dorsum, head, and limbs; male coloration; small to medium size; and by the short and narrow head.